Developing Method Use Of Tbm To User Information Literacy In Six Tbm Sambikerep Villages Surabaya City - Fahriyah, Fahriyah; Damayanti, Astrid (Record and Library Journal, 2017)
The existence of Community Library in Six PAUD Sambikerep Village, Â Sambikerep District Surabaya City expected can closer of resources in the community, causing exasperation reading (literacy) for PAUD mothers and parents of early childhood education, broaden knowledge in public life and certainly indirectly educate and improve lives the surrounding community. The purpose of this study to analyze the influence of the use of community library and information literacy of the PAUD Mother and Parent of Â early childhood of in the Sambikerep Village, Surabaya City. The population in this study were all Mother and Parents PAUD as Community Library users totaling 292 people. A sample of 64% from the population that found as many as 186 respondents. The sampling technique used in this study is the probability sampling is using simple random sampling. On average respondents about the use of TBM is 3.687 and the information literacy of users is 3,853. The reliably of the questionnare was calculated to be between 0.951 and 0.882 using the Cronbachs Alpha. The analysis Kolmogorov-Smirnov Test is Significant mean score of 0,000 that each variable were normal distribution. Hyphotesis test shows Î± (0.05)> Significancy (0.000) were significant and simultaneous relationship. Analysi Cooeficient using Product Moment Correlation Correlations scores was r = 0.669 with significant Ï = 0.000 <Î± = 0.05 were medium correlations. Significant correlations tcount Test score of 12.196 and Ttable at significantion score of 0.05 with 185 hp 2.34667 (R2) = 0,447 were positive and significant correlation between the use of TBM and the information literacy of users.